Metabolic and Immune Markers for Precise Monitoring of COVID-19 Severity and Treatment - Rendeiro, André F.; Vorkas, Charles Kyriakos; Krumsiek, Jan; Singh, Harjot K.; Kapadia, Shashi N.; Cappelli, Luca Vincenzo; Cacciapuoti, Maria Teresa; Inghirami, Giorgio; Elemento, Olivier; Salvatore, Mirella (Frontiers in Immunology, 2022)
Deep understanding of the SARS-CoV-2 effects on host molecular pathways is paramount for the discovery of early biomarkers of outcome of coronavirus disease 2019 (COVID-19) and the identification of novel therapeutic targets. In that light, we generated metabolomic data from COVID-19 patient blood using high-throughput targeted nuclear magnetic resonance (NMR) spectroscopy and high-dimensional flow cytometry. We find considerable changes in serum metabolome composition of COVID-19 patients associated with disease severity, and response to tocilizumab treatment. We built a clinically annotated, biologically-interpretable space for precise time-resolved disease monitoring and characterize the temporal dynamics of metabolomic change along the clinical course of COVID-19 patients and in response to therapy. Finally, we leverage joint immuno-metabolic measurements to provide a novel approach for patient stratification and early prediction of severe disease. Our results show that high-dimensional metabolomic and joint immune-metabolic readouts provide rich information content for elucidation of the host’s response to infection and empower discovery of novel metabolic-driven therapies, as well as precise and efficient clinical action.